Requesting Strategies in The Doorman Movie Using the Trosbrog's Theory (1995) - Alwiya Saboe; Hamzah A. Machmoed; Noer Jihad Saleh (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
In conducting this research, the researcher uses the descriptive qualitative method. This research is qualitative because the data are in the form of words and are analyzed based on the natural setting or context. this research to show the division of request strategy in speech act in the doorman movie. The doorman movie is an action genre movie which mostly from the data obtained is imperative. , the results reveal eight of Trosbrog's (1995) seven types of speech act techniques used by the characters in dialog in the movie entitled "The Doorman". Questioning the imperative strategy type of request speech act has the most data that is 16 data, and the willingness about 7 data and mild request and suggestory formulae, Statement of Obligation, Requesting as a statement of wish, permission and Statement of Speaker Wishes have the fewest data. Furthermore, the imperative strategy is very dominant in this case because the movie that Researcher uses is in the action genre, and what is unique is that the interlocutor after being given an imperative sentence or phrase and willingness and there are several or even indicating that there is no verbal answer but in a non-verbal way or we can say it as action as the answer.